2021
DOI: 10.3390/ijerph18073388
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance in Association with Thyroid Function, Psychoemotional State, and Cardiovascular Risk Factors

Abstract: Background: Individuals with insulin resistance (IR) have a high risk of diabetes or metabolic syndrome, and they are more likely to have depression. Furthermore, IR by itself is a major cardiovascular risk factor in healthy persons. Thus, we aimed to investigate IR in association with thyroid function, psychoemotional state, and cardiovascular risk factors among 45–84-year-old citizens of Palanga. Methods: A randomized epidemiological study was performed with 850 subjects. All participants were evaluated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…These results refer to the significant role of body weight in modulation of the link between metabolic features and thyroid function [25] .…”
Section: Discussionmentioning
confidence: 56%
“…These results refer to the significant role of body weight in modulation of the link between metabolic features and thyroid function [25] .…”
Section: Discussionmentioning
confidence: 56%
“…Area of research in thyroidology is the association of IR with thyroid functional and morphological abnormalities. Recent studies have shown consistent association of IR and thyroid morphological changes, raising the question of whether abnormality in glucose metabolism, which is a final consequence of IR, affects thyroid morphology [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Homeostasis model assessment for insulin resistance (HOMA-IR) is a model to assess insulin resistance based on fasting insulin and fasting glucose and has widely been investigated in relation to thyroid hormones and thyroid function. Literature reported both a negative association between HOMA-IR and both fT4 and fT3 in euthyroid participants (Roos et al 2007, Abdelwhab & Foda 2010, Bin Obead et al 2021, a positive association (Ren et al 2014 as no association at all (De Pergola et al 2007, Kazukauskiene et al 2021. In both hypothyroid and hyperthyroid patients, increased levels of HOMA-IR were found compared to euthyroid controls (Kapadia et al 2012, Srivastava et al 2021, although no difference between hypothyroid patients and euthyroid controls was found as well (Owecki et al 2006).…”
Section: Pancreas Homeostasis Model Assessment For Insulin Resistance...mentioning
confidence: 97%